Public Perception of The Instagram Account of PPL & KPM International 2025 in The Formation of The Image of STAIN Meulaboh - Zulpina; Heri Rahmatsyah Putra; Mutia Tisa (DAWUH : Islamic Communication Journal, 2026)
This study aims to analyze the role of the Instagram account @pplkpm_internasional_2025 in shaping public perception and the image of STAIN Teungku Dirundeng Meulaboh as an internationally-oriented Islamic university. This study is important because there has been no specific study that places students as non-professional communication actors in the management of social media for international programs in the PTKIN environment. This study uses a qualitative descriptive approach with digital observation techniques on 111 posts as the main unit of analysis during the period of January–October 2025, and in-depth interviews with seven informants consisting of account managers and followers as the main data sources. The results show that the consistency of posts, the use of international logos and slogans, and the dominance of educational and documentary content shape the public's perception that the account represents the institution's official program. Audience interactions, such as likes and comments, serve as social validation that reinforces the program's positive image. The main findings of this study indicate that interdisciplinary students, as non-professional communication actors, can effectively build the institution's image on social media without the direct involvement of the campus public relations unit. These findings expand the theoretical understanding of the formation of higher education institutions' images based on participatory digital communication. In practical terms, the results of this study imply that universities need to formulate guidelines for managing social media for international programs that strategically involve students. Keywords: Digital Image, Public Perception, International Program